Gene Expression Profiles of Entorhinal Cortex in Alzheimer's Disease. (September 2014) - Ding, Bingqian; Xi, Yan; Gao, Ming; Li, Zhenjiang; Xu, Chenyang; Fan, Shaokang; He, Weiya
The incidence of Alzheimer's disease (AD) has been increasing in the recent years but the underlying mechanisms remain uncertain. This study aimed to analyze the differentially expressed genes (DEGs) in entorhinal cortex with AD and identify featured genes related to AD. Gene expression profile GSE5281 was downloaded from Gene Expression Omnibus, including 10 AD and 13 control samples. Differentially expressed genes were identified by Student t test including 119 upregulated and 591 downregulated DEGs. Then, we obtained 14 enrichment Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways among which 11 pathways were significantly enriched (adjusted P value < .05). The KEGG pathway network which was constructed by 14 KEGG pathways showed that 6-phosphofructokinase, muscle type, phosphoglucomutase 1, aldolase A, and adolase C had high degree. Glycometabolism pathways network which was constructed by 4 glycometabolism pathways showed that adenosine triphosphate (ATP) synthase, H+transporting, mitochondrial F1 complex ATP5B, ATP5C1, ATP5D, and ATP5G1 had high degree related to ATP metabolism. These findings suggested that these genes with high degree may be the underlying potential therapeutic targets for AD.